Shifting Meaning of Heroism: A Comparative Study of Homer’s The Odyssey and Madeline Miller’s Circe - Daniel Wowiling; Tri Pramesti (Anaphora : Journal of Language, Literary, and Cultural Studies, 2026)
Although numerous studies on Circe have concentrated on feminist reinterpretation and female agency, comparatively limited attention has been given to the structural reconstruction of Odysseus' heroism itself, a gap increasingly pressing given the growing cultural prominence of mythological retellings. This study examines how heroism, as a culturally constructed concept, shifts across The Odyssey and Circe. Using Roland Barthes’ concept of the cultural code as a structuralist framework, it analyzes how Odysseus’ heroism, grounded in kleos, aretē, and timē in the Homeric epic, is reconstructed in Circe through modern ethical and psychological perspectives. While traits such as intelligence and endurance remain consistent, the ideological foundation of heroism shifts from collective honor and public glory toward moral accountability and interior consciousness, suggesting heroism is not a universal ideal but a culturally dependent construct reshaped through literary adaptation.